Perspectives of Internet privacy in Singapore. - Foo, Peow Neng. (2008)
The true potential of the Internet has yet to be realized due to issues such as privacy and data security. The perspectives of privacy on the Internet have not been well documented here in Singapore. Thus, our research aims to understand the perceptions of online privacy in the local context.